2013
DOI: 10.1016/j.scr.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells provide a niche for placental hematopoietic stem/progenitor cell expansion through broad transcriptomic modification

Abstract: Umbilical cord blood (UCB) is an attractive source of hematopoietic stem cells (HSCs). However, the number of HSCs in UCB is limited, and attempts to amplify them in vitro remain inefficient. Several publications have documented amplification of hematopoietic stem/progenitor cells (HSPCs) on endothelial or mesenchymal cells, but the lack of homogeneity in culture conditions and HSC definition impairs direct comparison of these results. We investigated the ability of different feeder layers, mesenchymal progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 59 publications
2
15
1
Order By: Relevance
“…This observation was in line with previous work by our group on E4-ECs effect on hematopoietic stem cell (HSC) expansion [8], [36]. Our results showed that without contact, E4-ECs were not capable of sustaining BCC survival under starvation.…”
Section: Discussionsupporting
confidence: 93%
“…This observation was in line with previous work by our group on E4-ECs effect on hematopoietic stem cell (HSC) expansion [8], [36]. Our results showed that without contact, E4-ECs were not capable of sustaining BCC survival under starvation.…”
Section: Discussionsupporting
confidence: 93%
“…Direct contact between haematopoietic cells and ECs is essential for the self-renewal and differentiation of HSPCs 45, 46, 47 . Compared with mesenchymal cells, ECs are more efficient at expanding umbilical cord blood-derived HSPCs 50 . Other angiocrine factors, such as prostaglandin E2 (PGE2) (refs 51, 52), pleiotrophin 53 and epidermal growth factor (EGF) 54 , drive haematopoietic reconstitution, which establishes ECs as a physiological repository of HSPC-supportive factors.…”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…This finding is in line with the observation that in murine HSC niches, both MSCs and endothelial cells are required for the HSC maintenance. [28][29][30] It will be interesting to learn whether MSCs together with endothelial cells or other cell types may allow for the in vitro expansion of HSCs/MPPs. Altogether, these data support our previous conclusion that testing for the erythroid potential of CD133 C CD34 C HSPCs provides a simple but meaningful assay to test for the presence of HSCs/MPPs.…”
Section: Discussionmentioning
confidence: 99%